Advancing Minds: Critical Thinking Pedagogies in Indonesian EFL High School Speaking Lessons - Hamzah Puadi Ilyas; Wini Tarmini (Journal of English Language Studies, 2026)
Critical thinking is increasingly recognized as an essential component of English language teaching, yet its integration into speaking instruction in high school settings remains limited. This study aims to examine the pedagogical strategies Indonesian high school EFL teachers use to foster critical thinking during speaking activities. The research was conducted in eight Indonesian cities with nineteen English teachers from public and private high schools. Data were collected through in-depth semi-structured interviews and document analysis of lesson plans. Using a qualitative methodological design, athematic analysis approach was used to interpret the data. The findings showed that teachers promoted critical thinking through three main strategies: designing thought-provoking speaking tasks connected to real issues, scaffolding reasoning through purposeful and open-ended questions, and encouraging dialogic interaction that supported reflective peer exchange. These strategies helped students examine ideas, justify positions, and respond with greater clarity. The study concludes that speaking lessons can serve as a meaningful space for developing critical thinking when teachers intentionally design tasks and interactional structures that support deeper reasoning. The implications highlight the need for teacher education programs to emphasize practical models of questioning and collaborative speaking tasks and encourage schools to provide supportive environments for critical thinking-oriented pedagogy.